Determining over ground running speed using inertial sensors - Neville, J.; Rowlands, D.; Wixted, A.; James, D. (Procedia Engineering, 2011)
Accurate activity monitoring techniques provide coaches and athletes with the tools to better analyze the effect of training sessions in the lead up to competition. The most common approach for monitoring elite level athletes comes in the form of using Global Position Systems (GPS) in an effort to obtain the time spent running in different speed levels as well as recording the total distance travelled. Accelerometers, on the other hand, are steadily growing in popularity as activity monitoring tools and offer researchers, coaches and players an alternative way to track athlete performance. Accelerometers have previously been used to approximate running speeds and energy expenditure in athletes running on a treadmill. It is often argued both by athletes and researchers that the biomechanical processes involved in treadmill running differ significantly when compared to over ground running. This paper extends previous research by exploring the use of accelerometers to accurately approximate over ground running speeds. Performance monitoring units were placed in a specially designed vest, that when worn by the player, positioned the tracking unit around the middle to upper thoracic vertebrae. An experiment was conducted in which the accelerometry data for experienced runners over a range of speeds was recorded alongside an external speed measurement. Participants were asked to run a series of 50 m stretches of track at what they perceived to be constant speeds. Players were asked to steadily increase their speed for each trial, beginning roughly at 8 km/h and finishing at around 30 km/h. The accelerometer data was exported to MATLAB where a series of post processing steps were used to extract the stride frequency. The stride frequency derived from the accelerometer data was compared to an externally measured speed and found to produce a linear relationship as expected from the literature. This research has provided the ground work for the use of accelerometers in measuring the speed of over-ground running.